Citrate coated iron oxide nanoparticles: Synthesis, characterization, and performance in protein adsorption - Denise Arrozarena Portilla; Arturo A. Velázquez López; Rosalva Mora Escobedo; Hernani Yee Madeira (AIMS Materials Science)
Magnetic nanoparticles (MNPs) are extensively utilized in biomedicine as part of controlled drug release systems, hyperthermia, and magnetic resonance imaging. Surface modification of MNPs not only enhances their stability and biocompatibility but also increases affinity with certain molecules, allowing them to be used in protein separation and adsorption processes. This article reports the synthesis and characterization of iron oxide MNPs functionalized with citric acid (IONPs@CA) to evaluate their performance in protein adsorption. The nanoparticles were characterized using various techniques such as transmission electron microscopy (TEM), X-ray diffraction (XRD), dynamic light scattering (DLS), thermogravimetric analysis (TGA), and Fourier-transform infrared spectroscopy (FT-IR). The percentage of lysozyme (Lyz) adsorbed by IONPs@CA was 84.9%, while the IONPs sample only adsorbed 5.9%. In silico evaluation results showed some repulsion bonds obtained in Lyz-IONPs and hydrogen bonds, carbon-hydrogen bonds, and van der Waals interactions in Lyz-IONPs@CA. These results may be novel since no previous research was found specifying this type of interaction between lysozyme and IONPs and/or IONPs@CA. The maximum adsorption efficiency obtained for the coated nanoparticles was 88.3%.